Relatively young thick disks in star-forming late-type galaxies - Sattler, Natascha; Pinna, Francesca; Comerón, Sebastien; Martig, Marie; Falcón-Barroso, Jesus; Martín-Navarro, Ignacio; Neumayer, Nadine (Astronomy and astrophysics, 2025)
Aims. We trace the evolution of eight edge-on star-forming disk galaxies by analyzing stellar population properties of their thin and thick disks. These galaxies have relatively low stellar masses (4 × 10 9 -6 × 10 10 M⊙). Methods. We used Multi-Unit Spectroscopic Explorer (MUSE) observations and a full-spectrum fitting to produce spatially resolved maps of the ages, metallicities, and [Mg/Fe] abundances, and we extracted the star formation histories of the stellar disks. Results. Our maps show thick disks that are older, more metal-poor, and more [Mg/Fe]-enhanced than thin disks on average. The age differences between thin and thick disks are small (about 2 Gyr), however, and the thick disks are younger than previously observed in more massive and more quiescent galaxies. The thin and thick disks both show mostly sub-solar metallicities, and the vertical metallicity gradient is milder than previously observed in similar studies. The [Mg/Fe] differences between thick and thin disks are not sharp. The star formation histories of thick disks extend to recent times, although most of the mass in young stars was formed in thin disks. Conclusions. Our findings show thick disks that are different from the old quiescent thick disks that were previously observed in galaxies with different morphologies and/or masses. We propose that the thick disks in these galaxies did not form quickly at high redshift, but formed slowly over an extended time. The thin disks also formed slowly, but a larger mass fraction was created at very recent times.